Optimalisasi Sim Online Sebagai Strategi untuk Mewujudkan Pelayanan Prima pada Kantor Satpas Jember - Agnes Juwita* (Airlangga Development Journal, 2018)
Service  reform  in  Indonesia  has  links  with  decentralization.  The  aim  of  implementing  service  reforms throughout Indonesia is to improve service quality so as to create public trust in the government. The problem of SIM services is one of the internal problems in terms of service to the community. Therefore, SIM services must be excellent in accordance with the standards of the technological era that is growing at this time. Seeing this development, the Chief of the Republic of Indonesia National Police (Kapolri) General Police M. Tito Karnavian launched a future program for the National Police which is called the Promoter program.  Promoter  main  policy, focused   on   3   (three)   main   substances,   namely   Improved   Performance, Improved    Culture    and    Media Management.  SIM  Services  in  the  Administrative  Unit  of  the  SIM Administration (SATPAS) of the Jember Police Department itself, based on the pre-survey conducted by the service researchers in making and extending the SIM,  were  still  inadequate  or  had  not  yet  achieved excellent  service,  especially  regarding  Polri's  human resources at Samsat Jember. hampered by a good understanding  of  e-policing  policies.  In  connection  with these   problems,   the   Jember   Police SIM Administration Unit (SATPAS) conducted an opinion poll (survey questionnaire) during January to April 2015. The online service system is a form of government policy based on Presidential Instruction (Inpres) No. 3 of 20043 about national  policies  and  strategies  for  the  development  ofe-government. The basic reason for the emergence of online services is to eliminate the practice of brokering and to reduce criminal acts of corruption within the National Police. Then also to increase  community satisfaction inthe  realization  to  become  administrative  citizenship,  which  is related to the ownership of a Driving License (SIM). Seeing this reality, it becomes interesting to conduct research on the problem with the title “Optimalisasi SIM Online Sebagai Strategi untuk Mewujudkan Pelayanan Prima pada Kantor Satpas Jember ”.